Digital Putri Tangguk as a Medium to Identify the Building Elements of Short Stories for Middle School Students - Khomsatun Yuliatun; Rustam; Irma Suryani; Priyanto (Journal for Lesson and Learning Studies, 2025)
Folktales are an essential component of cultural heritage that convey moral values, ethics, and collective identity. One such folktale with high educational potential is Putri Tangguk, which is rich in character values and presents social and moral conflicts relevant for fostering students’ critical thinking skills. This study aims to develop and evaluate the effectiveness of the Putri Tangguk folktale in an interactive digital format as a learning medium to enhance students’ understanding of narrative structure, character education, and social relationships. A case study approach was employed, involving language teachers and junior high school students as research participants. Data were collected through in-depth interviews, participatory observation, documentation, and focus group discussions. The data were analyzed qualitatively using thematic analysis. The results indicate that the implementation of the digital Putri Tangguk folktale significantly increased student engagement and enthusiasm during the learning process. Students demonstrated improved ability to identify elements of short stories and a deeper understanding of the social and moral values embedded in the narrative. Moreover, the use of digital media enhanced students’ technological literacy and supported a more interactive learning experience. These findings suggest that the integration of digitalized folktales can serve as an effective educational tool for promoting critical thinking and cultural understanding in language learning contexts.